Strategi Pengembangan Sumber Daya Manusia dalam Mengatur Pantai Goa Petapa - Hidayati, Nurul; Faidal, Faidal (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
The purposesthis study are to determine the strategy of human resources developmentat Goa Petapa Beach, the supportingand its bottleneck factors. The type of study is descriptive qualitative. The data were collected byobservation, and deep interview.There are 3 selected informants in this study.The results showed that the human resources development strategy were unoptimal and even still stagnand. The strategy is still in a plan, and the obstacles have caused the slow down the in managing the Goa Petapa beach. The supporting factor is the Goa Petapa beach, which is strategic located that near the Suramadu bridge and the University of Trunojoyo Madura. Meanwhile, the obstacles factors are inadequate facilities, infrastructure that need improvement, and the human resources have unskill labor. There is not training tourism programs.